(untitled) (Academia Journal of Medicine, 2021)
Background: Tuberculosis is an old disease and has deep social impact on the society. It is an re-emergent killer disease with rise in MDR and XDR strains. DOTS strategy has had a substantial impact over past few decades. Monitoring outcome of TB treatment is very much important in evaluating the effectiveness of tuberculosis control program. Keeping in view all of these facts, it was decided to study compliance and outcome of newly diagnosed cases of Tuberculosis, subjected to short course chemotherapy regimen under DOTS. Subjects and Methods: The study was a prospective cross sectional study conducted in newly diagnosed cases of Tuberculosis, subjected to short course chemotherapy regimen (DOTS). Medical records of all TB patients registered from April 2020 to 31 October 2020 were reviewed. Tuberculosis types, HIV and Diabetes status, as well as treatment outcomes were categorized according to RNTEP guidelines. Results : Out of total 663 patients, 408 (61.53%) were males and 225 (38.47%) were females. Male to female ratio was observed to be 1.60:1. The mean age of males was 40.02 ± 14.04 and mean age of females was 36.15 ± 14.82. 57.02% patients were having pulmonary Tuberculosis and 42.98% patients were having extra pulmonary tuberculosis. Treatment outcome among total 663 patients was as follows – 288 (43.43%) patients got cured, 251 (37.85%) completed treatment, 55 (8.29%) dies, 8.76 (5.88%) were lost to follow up (defaulter) and 30 (4.52%) failed treatment. Conclusion: The treatment success rate of tuberculosis patients was adequate (81.28%) in relation with national targets. Again easy accessibility of healthcare services are required to further improve the compliance of TB treatment.